Business Sustainability Performance (BSP) quantifier for Malaysia context - Faiz, Mohd Turan; Kartina, Johan; Chui Sheng, Tay (Springer Singapore, 2018)
Sustainable development has become a topic of interest among government, non-profit organisation and industrial players across the globe. In Malaysia, sustainable performance has always been a great concern as the government has taken actions to promote sustainability practices. However global surveys show that Malaysia is not performing as expected and there is a need for a solution to improve sustainability consciousness among the industry of Malaysia. This paper presents of the background knowledge for the Business Sustainability Performance (BSP) quantifier, the methods of development, the experimental results and discussion on the results.